Incidência e resultados do tratamento da retinopatia da prematuridade no Hospital de Clínicas de Porto Alegre, Brasil - Borges Fortes Filho, João; Barros, Cristiano Koch; Eckert, Gabriela Unchalo; Procianoy, Leticia; Procianoy, Renato Soibelmann (Clinical and Biomedical Research, 2007)
Introduction: Retinopathy of prematurity is a leading cause of blindness in children. This paper aims to evaluate the incidence, the rate of diode laser treatment and the six-month outcomes in all very low birth weight preterm infants from Hospital de Clínicas de Porto Alegre, Brazil, between October 2002 and October 2006, screened for the disease according to the Brazilian recommendations. Methods: A prospective cohort was conducted on 322 premature children with birth weight ≤1.500 grams or a gestational age at birth ≤32 weeks. All patients were examined by indirect binocular ophthalmoscopy with pupil’s dilation after the 6th week of life. The examination were repeated depending on the disease classification. Results: Retinopathy of prematurity occurred in 82 infants in an incidence rate of 25.47%. Threshold disease occurred in 18 of the patients (5.59%). All of them had the disease affecting posterior Zone II needing laser treatment under general anesthesia or sedation in the Neonatal Intensive Care Unity. Three of the treated children needed a second laser session. One patient of the re-treated group needed scleral buckling surgery with an equatorial silicon band after progression for stage 4 of ROP. One patient missed the opportunity for laser and the disease progressed to stage 5 of ROP and blindness. Conclusions: The incidence of retinopathy at our institution was similar to international results and also the percentage of threshold disease needing treatment. Laser photocoagulation was effective to stabilize the disease among 17 treated patients. One non-treated patient had evolution for blindness.